The Compilation of Competitive Strategy with SWOT Analysis Approach at Bali Tropic Resort & Spa - Ni Putu Chintya Kumala Dewi; I P M Astawa; I M Wijana (Jurusan Akuntansi Politeknik Negeri Bali, 2021)
This study aims to determine the competitive strategy adopted the Bali Tropic Resort & Spa. The subjects in this study were 14 department head managers. This research was tested using a SWOT analysis, namely by identifying various internal and external factors of the company. The analysis of internal factors (strengths and weaknesses) and external factors (opportunities and threats) which were then formulated in the SWOT Diagram and SWOT Matrix. From the results of the analysis on the SWOT diagram, it appears that the position of the Bali Tropic Resort & Spa is located in Quadrant I, which shows that Bali Tropic Resort & Spa faces several opportunities and has various forces that drive these opportunities and it is recommended to carry out the SO strategy by taking advantage of opportunities. Based on the SWOT matrix, the SO strategy that companies can implement is to take advantage of increasingly sophisticated technological developments to facilitate promotional activities and make packages that attract guests' attention.